Common Factors, Information, and Holdings Dispersion - Fontaine, Patrice; Jimenez-Garcès, Sonia; Seasholes, Mark S (Review of Finance, 2018)
Abstract We derive closed-form solutions for asset prices and portfolio holdings when agents have asset-specific information and/or information about common components that affect many assets. Our solutions are general, encompass existing information structures, and are used to analyze new structures. A given investor’s portfolio can exhibit highly disperse holdings—e.g., portfolio weights may vary significantly from market capitalization weights. Our model also generates large ranges of asset prices due to information asymmetries. We help explain why US investors (e.g.) may underweight German stocks (e.g.) on average, but overweight a particular German stock relative to its market capitalization weight.